2023
DOI: 10.1055/a-2014-4350
|View full text |Cite
|
Sign up to set email alerts
|

Kriterien zur Evaluation des Ansprechens auf Biologika bei schwerem Asthma – der Biologics Asthma Response Score (BARS)

Abstract: Zusammenfassung Hintergrund Die Einführung monoklonaler Antikörper (Biologika) hat die Therapie des schweren Asthmas revolutioniert. Auch wenn die Mehrheit der Patienten ein Ansprechen zeigt, kann dieses unterschiedlich ausgeprägt sein. Bislang sind Kriterien zur Beurteilung des Ansprechens auf Biologika nicht einheitlich definiert. Ziel Definition von konkreten, einfachen und praxistauglichen Kriterien zur Bewertung des Ansprechens auf Biologika bei Patienten mit schwerem Asthma, um eine E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…The main advantage of our study is the classification of our treated patients in responder and non-responder according to the novel BARS Score that as universally applicable to classify mAb-therapy response. 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantage of our study is the classification of our treated patients in responder and non-responder according to the novel BARS Score that as universally applicable to classify mAb-therapy response. 25 …”
Section: Discussionmentioning
confidence: 99%
“…All pulmonary function tests (PFT) were performed under continued stable inhaled therapy. Responder status was assessed using Biologics Asthma Response Score (BARS) recently published by Milger et al 25 Patients classified “responder” or “partial responder” were grouped in the “responder group”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a German consensus group published the BAR-Score, a scoring system for biologic therapy response in severe asthma allowing for easier and more objective treatment comparisons. [22] Calculated through assessment of ACT, annualized exacerbation rate and reduction of steroid dose, BARS allows for categorization of biologic recipients into "good response", "intermediate responders" and "insu cient response". [22] Using BARS, we found that around half of all patients attained a good response, with another quarter showing intermediate response, irrespective of group.…”
Section: Discussionmentioning
confidence: 99%
“…A higher score corresponds to a better therapy response, with the overall response being assessed using the average of all three categories, allowing for categorization of therapy response into one of three categories ("good response", "intermediate responders" and "insu cient response"). [22]…”
Section: Data Collectionmentioning
confidence: 99%